2017
DOI: 10.1038/s41598-017-02960-1
|View full text |Cite
|
Sign up to set email alerts
|

XBP1-FoxO1 interaction regulates ER stress-induced autophagy in auditory cells

Abstract: The purpose of this study was to clarify the relationship among X-box-binding protein 1 unspliced, spliced (XBP1u, s), Forkhead box O1 (FoxO1) and autophagy in the auditory cells under endoplasmic reticulum (ER) stress. In addition, the relationship between ER stress that causes unfolded protein response (UPR) and autophagy was also investigated. The present study reported ER stress induction by tunicamycin treatment that resulted in IRE1α-mediated XBP1 mRNA splicing and autophagy. XBP1 mRNA splicing and FoxO1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 80 publications
(66 reference statements)
2
51
1
Order By: Relevance
“…FOXO1 has been reported to act as a tumor suppressor for MM (76). The activation of FOXO1 could subsequently inhibit the tumor growth and induce cell autophagy and cell death (77)(78)(79)(80). FOXO3, another family member of the FOXO family, has been studied in MM (81).…”
Section: Discussionmentioning
confidence: 99%
“…FOXO1 has been reported to act as a tumor suppressor for MM (76). The activation of FOXO1 could subsequently inhibit the tumor growth and induce cell autophagy and cell death (77)(78)(79)(80). FOXO3, another family member of the FOXO family, has been studied in MM (81).…”
Section: Discussionmentioning
confidence: 99%
“…XBP‐1 protein then interacts with the promoters of several genes involved in UPR and ER‐assisted degradation in order to restore protein homeostasis and promote cytoprotection . For regulation of ER stress–induced autophagy, IRE1α activates the XBP1–FOXO1 interaction and TNF receptor–associated factor 2–apoptosis signal‐regulating kinase 1/JNK cascade . XBP‐1 mRNA splicing also triggers autophagy through transcriptional activation of Beclin 1 .…”
Section: Molecular Regulation Of Autophagy Machinerymentioning
confidence: 99%
“…It has been reported that ER stress is accompanied with autophagy that may promote cellular survival (29,50). Autophagy is a catabolic process that degrades and recycles damaged macromolecules and organelles (29,51).…”
Section: Discussionmentioning
confidence: 99%